Fabrication and application of electrochemical sensor for analyzing hydrogen peroxide in food system and biological samples. (15th August 2022) - Xing, Lujuan; Zhang, Wangang; Fu, Lijuan; Lorenzo, José Manuel; Hao, Yuejing
Highlights: The fabrication of electrochemical sensors was reviewed with enzyme and non-enzyme types on detecting H2 O2 . Electrochemical sensors showed remarkable stability, repeatability and sensitivity on H2 O2 signal. The limit and future perspective of electrochemical sensor on H2 O2 detection was discussed. Abstract: Hydrogen peroxide is an active mediator in biological processes and thus the detection of hydrogen peroxide is necessary for the foods, medicals, pharmaceutical, and chemical industries. Compared with the traditional methods, the electrochemical sensor is investigated as a sensitive, efficient, and time-saving method for the detection of hydrogen peroxide. In order to update the latest research, the current review focused on the modification of electrodes, linear range, detection limit as well as the applications of novel electrochemical sensors. In special, the recovery, sensitivity as well as limitations of hydrogen peroxide sensors in food or biological samples were revealed, which was supposed to supply the references and provide direction for future research.